Dichotomic Potency of IFNγ Licensed Allogeneic Mesenchymal Stromal Cells in Animal Models of Acute Radiation Syndrome and Graft Versus Host Disease - Chinnadurai, Raghavan; Bates, Paul D.; Kunugi, Keith A.; Nickel, Kwangok P.; DeWerd, Larry A.; Capitini, Christian M.; Galipeau, Jacques; Kimple, Randall J. (Frontiers in Immunology, 2021)
Mesenchymal stromal cells (MSCs) are being tested as a cell therapy in clinical trials for dozens of inflammatory disorders, with varying levels of efficacy reported. Suitable and robust preclinical animal models for testing the safety and efficacy of different types of MSC products before use in clinical trials are rare. We here introduce two highly robust animal models of immune pathology: 1) acute radiation syndrome (ARS) and 2) graft versus host disease (GvHD), in conjunction with studying the immunomodulatory effect of well-characterized Interferon gamma (IFNγ) primed bone marrow derived MSCs. The animal model of ARS is based on clinical grade dosimetry precision and bioluminescence imaging. We found that allogeneic MSCs exhibit lower persistence in naïve compared to irradiated animals, and that intraperitoneal infusion of IFNγ prelicensed allogeneic MSCs protected animals from radiation induced lethality by day 30. In direct comparison, we also investigated the effect of IFNγ prelicensed allogeneic MSCs in modulating acute GvHD in an animal model of MHC major mismatched bone marrow transplantation. Infusion of IFNγ prelicensed allogeneic MSCs failed to mitigate acute GvHD. Altogether our results demonstrate that infused IFNγ prelicensed allogeneic MSCs protect against lethality from ARS, but not GvHD, thus providing important insights on the dichotomy of IFNγ prelicensed allogenic MSCs in well characterized and robust animal models of acute tissue injury.